Slide tracheoplasty: Predictors of outcomes and literature review. (March 2020) - Wertz, Aileen; Fuller, Stephanie M.; Mascio, Christopher; Sobol, Steven E.; Jacobs, Ian N.; Javia, Luv
Abstract: Objective: Determine preoperative comorbidities and intraoperative parameters associated with adverse postoperative outcomes. Methods: Retrospective case series at a single tertiary care children's hospital from 2010 through 2017. Results: Twenty-six patients with median age of 6 months and median weight of 7.1 kg underwent slide tracheoplasty. Median time to extubation, length of intensive care unit admission, and length of hospitalization were 7, 27, and 30 days, respectively. Twenty-two (85%) required no additional intervention. Overall success was 87%. One (4%) patient required open revision, and 3 (11%) required tracheostomy. Concomitant cardiac surgery was associated with postoperative tracheostomy (p = 0.04). Age and weight at surgery were inversely correlated with length of intubation (p = 0.03) and length of hospital stay (p = 0.001, p = 0.002) respectively. Hospital stay was 2.2 times longer if preoperative mechanical ventilation was required (p = 0.01) and 39% longer for every 1 mm decrease in airway diameter at the narrowest portion of the stenosis (p = 0.005). There were no deaths related to persistent tracheal stenosis with a median follow-up of 24 months. Conclusion: Slide tracheoplasty is safe and effective. Concomitant cardiac surgery was associated with postoperative tracheostomy. Lower age and weight at surgery were correlated with longer length of intubation and hospital stay. Preoperative mechanical ventilation and smaller airway diameter were associated with longer hospital stay. This information may be helpful in counseling families and planning future prospective studies.